LEADING WITH INTEGRITY. Issue 91 (10th September 2018) - O'Rourke, Bill
Abstract: O'Rourke, a retired, longtime Alcoa senior executive, believes integrity is the most crucial differentiator for a great leader. He discusses examples of ethical dilemmas he navigated in his years with the company, including especially thorny situations when he was president of Alcoa‐Russia. He explains nuances of the concept of conflicts of interest, and writes about Paul O'Neill, Alcoa's chief executive officer (CEO) when O'Rourke worked there. O'Neill articulated a vision to be the best corporation in the world, particularly around the importance of worker safety. During O'Neill's 13‐year tenure as CEO, "Alcoa became known as the safest manufacturing corporation in the world because O'Neill made safety a true value in the company, " O'Rourke writes.